La production de l’espace - Анри Лефевр; Светозар Эфиров (Russian Sociological Review, 2011)
An excerpt from the book by Henri Lefebvre introduces the basic principle of his theory  and  what is followed by explanations and implications. The main point -- space (social) is the product (social) -- is considered in the problematic vein. The author wonders about what hides this truth of (social) space, which consists in that it is the product (social). His response is --  a double illusion, each side of which suggests another, reinforce each, it is justified: first, the illusion of transparency, and second -- of density ("realistic" illusion). What follows is a detailed analysis of these illusions.